Annual Reports: Fact or Fiction? Are There Governance Implications? - Garrow, Nigel Stephen; Awolowo, Ifedapo Francis; Growe, Glenn A (Journal of Leadership, Accountability and Ethics, 2019)
Two recent high-profile announcements of companies going into administration (Palmer & Harvey) and liquidation (Carillion) raise questions about the robustness of statements made in annual reports including the quality and objectivity of audit reporting, and the implications of this on Corporate Governance practice. This discussion coincides with the Financial Reporting Council 'Proposed Revisions to the UK Corporate Governance Code', December 2017. This paper considers some of the behavioural factors which influence performance and, most likely, performance reporting. It also considers some of the potentially fraudulent activity by firms, and the quality and nature of audit reporting in Annual Reports. Contexts of this paper are Agency Theory and Merger and Acquisition (M&A) activity. The next step in this research will be to increase the sample size and explore the scale of the issues being considered, and then develop recommendations for both corporate reporting narratives in Annual Reports, and the adoption of forensic accounting techniques in audit reporting.